Utjecaj novih medija na jezik mladih u pisanim radovima - Filipan, Blaženka (Slavistična revija, 2016)
In the article, the authors investigate whether eighth-graders use elements of the language of new media in their texts written at school, for school, or in their spare time, such as: anglicisms, abbreviations, emoticons, multiple punctuation marks, and other graphostylistic devices. Based on the results of the research, it is evident that eighth-graders very often use all the elements that are characteristic features of the language of new media in the texts written in their spare time whereas they hardly use them in their school assignments.
Keywords: abbreviations; anglicisms; anglizmi; communication; elemetary schools; emoticons; emotikoni; internet; jezik; komunikacija; kratice; Language; language of new media; novi mediji; osnovna šola; pisna besedila; primary school; written texts